Investigation of the gas-liquid-particle multi-phase hydrodynamics of Wemco flotation cells. (30th March 2022) - Schwarz, M.P.; Koh, P.T.L.; Yang, W.; Nguyen, B.
Highlights: CFD model of 1.3 m 3 Wemco 56 and 92 m 3 Wemco 225 cell flotation cells developed. Single phase CFD simulation flow field agrees well with measured velocities. Three-phase (three-fluid) CFD model developed together with population balance. Three phase CFD simulation accords with bubble and solids measurements. Voidage predicted by CFD model of Wemco 225 cell agrees with plant measurements. Abstract: Computational Fluid Dynamics (CFD) modelling of a 1.3 m 3 flotation cell fitted with a Wemco 56 mechanism has been performed, backed up by experimental measurements. The flow field, gas dispersion and solids concentration in the flotation cell were studied. Both the PIV measurements and CFD modelling of the cell revealed that the rotor generated a jet stream towards the wall, which induced two strong vortices, one below the rotor level and the other extending from the rotor region to near the free surface. The strong downward flow along the wall of the tank turns horizontally passing underneath the false bottom and up through the draft tube. Inside the draft tube, an average axial velocity of about 0.7 m s −1 with a flow rate of 0.05 m 3 s −1 was predicted, in good agreement with experiment. The void fraction was found to vary significantly with height in the cell. The maximum value of void fraction reached 0.55 near the froth interface in the air–water system. In the presence of solids, the air bubbles were able to penetrate further downwards to the bottom of the tank and the void fraction reached a maximum value of 0.35 near the froth interface. The Sauter mean bubble diameter was found to be in the range of 0.3–0.9 mm in the air–water system. The solids concentration was practically uniform throughout the tank except for the region near the surface. CFD simulation results for velocity, bubble size, void fraction and solids concentration are analysed in detail. CFD simulation was then carried out for an industrial-scale Wemco 225 cell (92 m 3 ). Predictions are similar to those for the smaller Wemco 56, though there are differences in detail. Voidage predicted by CFD model of the Wemco 225 cell agrees with plant measurements.